Bloomsday: James Joyces Ulysses Celebrated as Theatrical Event - Willmar Sauter (Culture Unbound: Journal of Current Cultural Research, 2009)
James Joyce had decided that 16 June 1904 should be the one day in the life of Leopold Bloom, about which he wrote his 800 page novel Ulysses. In his book, Joyce actually followed Mr Bloom that entire day, from his getting up and having the nowadays famous kidney breakfast, to the late evening, when he had to break into his own house on 7 Eccle Street to have a drink with Stephen Dedalus, the other main figure of the novel. The centenary of that very day took, accordingly, place in 2004. I have borrowed the identity of Mr Bloom to describe some street scenes from the centennial celebrations of Bloomsday in Dublin. After this introductory presentation, part two of this article will attempt to analyse Bloomsday in terms of a Theatrical Event, embedded in an unusual and striking playing culture. In a third part, Mr Bloom will once more be allowed to make some concluding comments.